Understanding Household Water Demand for Metro Cebu - Cristina C. David; Arlene B. Inocencio; Francisco M. Largo (Philippine Institute for Development Studies (PIDS), 1998)
Due to the rapid population growth in cities and the rising cost of developing new sources of water supply, Metro Cebu has experienced an increasing demand and supply gap. This has been exacerbated by the current drought and the pollution on bodies of water surrounding the city. Efficient water utilization entails the adoption of an optimal pricing framework to mitigate the externalities imposed by production and consumption of water. This study examines the nature and determinants of water demand in the Metro Cebu households. Estimates show that optimal pricing strategy can be an effective means of addressing the scarcity of freshwater supply. The relatively high water prices reflect the cost of distribution and monopoly profits, both of which can be reduced through expanding and making accessible the central distribution system.
Keywords: 330; water sector; pricing strategy; water demand